Seroprevalence of Antibodies against Pkn1, a Novel Potential Immunogen, in Chlamydia trachomatis-Infected Macaca nemestrina and Human Patients. (18th June 2014) - Patel, Achchhe L.; Mishra, Prashant K.; Sachdev, Divya; Chaudhary, Uma; Patton, Dorothy L.; Saluja, Daman
Abstract : Chlamydia trachomatis (CT) is an important cause of sexually transmitted genital tract infections (STIs) and trachoma. Despite major research into chlamydial pathogenesis and host immune responses, immunoprotection has been hampered by the incomplete understanding of protective immunity in the genital tract. Characterized vaccine candidates have shown variable efficacy ranging from no protection to partial protection in vivo . It is therefore a research priority to identify novel chlamydial antigens that may elicit protective immune responses against CT infection. In the present study we assessed the seroprevalence of antibodies against protein kinase1 (Pkn1), DNA ligaseA (LigA), and major outer membrane protein A (OmpA) following natural CT infection in humans and in experimentally induced CT infection in Macaca nemestrina . Antigenic stretches of Pkn1, LigA, and OmpA were identified using bioinformatic tools. Pkn1, LigA, and OmpA genes were cloned in bacterial expression vector and purified by affinity chromatography. Our results demonstrate significantly high seroprevalence of antibodies against purified Pkn1 and OmpA in sera obtained from the macaque animal model and human patients infected with CT. In contrast no significant seroreactivity was observed for LigA. The seroprevalence of antibodies against Pkn1 suggest that nonsurface chlamydial proteins could also be important for developing vaccines for C. trachomatis .